2018
DOI: 10.1111/pace.13447
|View full text |Cite
|
Sign up to set email alerts
|

Electroanatomic mapping‐guided localization of alternative right ventricular septal pacing sites in children

Abstract: EAM-guided procedures have been useful to reduce radiation exposure and to localize RVAPS with narrower paced QRS and lower GLS than RVA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…In the last few years, alternative pacing sites in pediatric pacing have been more commonly used, either with endocardial pacing in the right ventricle 18,19 or with epicardial pacing in the LV. Retrospective studies in children have consistently shown that LV pacing is safe and effective in preserving LV synchrony and function 8‐9,20‐22 …”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, alternative pacing sites in pediatric pacing have been more commonly used, either with endocardial pacing in the right ventricle 18,19 or with epicardial pacing in the LV. Retrospective studies in children have consistently shown that LV pacing is safe and effective in preserving LV synchrony and function 8‐9,20‐22 …”
Section: Discussionmentioning
confidence: 99%
“…EAM has been shown to significantly reduce fluoroscopy times with single [ 52 , 53 ], dual [ 16 , 54 , 55 ], and CRT devices [ 15 , 30 , 56 ]. For traditional CRT devices, the most time-consuming and fluoroscopic-dependent step is the cannulation of the CS os with the guide sheath.…”
Section: The Obsolescence Of Fluoroscopy—transition To Alternate Imag...mentioning
confidence: 99%
“…Authors suggest that the EnSite Velocity system is a useful adjunct to minimize fluoroscopy use for device implantation procedures in children, especially for those with repaired congenital heart defects, whereas cost and longer procedure times are of concern. Silvetti et al 31 has also implanted single‐ and dual‐chamber pacemakers in pediatric patients (complete AVB) with the aid of the EnSite Velocity system, while localizing alternative right ventricular sites with narrower paced QRS.…”
Section: Ensite Systemmentioning
confidence: 99%